Review on 5G NR LDPC Code: Recommendations for DTTB System - Fengshuang Li (IEEE, 2021)
The freeze of the 5th generation new radio (5G NR) Release 16 indicates that 5G development has stepped into a new stage. The application of a dedicated low-density parity-check (LDPC) code for channel coding is an important technical advance that distinguishes 5G NR from the 4th generation (4G) long-term evolution (LTE) and LTE-advanced. Although LDPC codes have been used in many different systems, the newly developed LDPC code in 5G NR integrates many cutting-edge technologies to provide better performance and attractive features. Thus, it can be a good reference for channel coding in other evolving systems headed by digital terrestrial television broadcasting (DTTB). In emerging applications, the DTTB system needs to carry information with higher density, while meeting the high requirements for real-time, coverage, and bit error rate of broadcasting. To provide a reference for DTTB channel coding that improves its performance and supports new services, a review of 5G NR LDPC code implementation is carried out from three aspects: code analysis and design, decoding algorithm, and decoder architecture. We thoroughly evaluate each solution and highlight some candidates for existing implementations or directions for further development of the DTTB system.